MODEL KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Bahrul Ulum; Umi Kulsum; Mujiyatun (UNISAN JURNAL, 2023)
The focus of this research is; (1) How is the leadership model used by the head of MTs Darul Ulum (2) How is the strategy developed by the Head of MTs Darul Ulum in improving the pedagogical competence of teachers of Religious Education, and then (3) What is the impact of leadership strategies to increase headmaster Pedagogic Competence SKI teacher at MTs Darul Ulum. Lempuyang Pesawaran. Thus this study aims (1) to reveal the head of the leadership model of MTs Darul Ulum in improving the pedagogical competence of teachers of Religious Education, (2) to describe what the strategy undertaken by clod MTs Darul Ulum in improving pedagogical Teachers of Religious Education, and (3 ) To determine the impact of headmaster’s leadership strategy to increase Pedagogic Competence SKI teacher at MTs Darul Ulum. This study used a qualitative approach, data collection with interview techniques, observation, and documentation. Data analysis techniques with interactive analysis model. To check the validity of the data is done with credibility, Transferability, dependability, confirmability. The results showed that: (1) Leadership Model MTs Darul Ulum Head of Lempuyang in Improving Teacher Pedagogic Competence SKI applied is more oriented on the pattern of situational leadership (2) Principals Strategies In Improving Teacher Pedagogic Competence SKI is to use: 1) Ability manage the class, 2) the ability of the teaching system, and 3) the ability of the arrangement of the classroom climate. And to (3) Impact of Principals Leadership Strategies Against Increased SKI Teacher Pedagogic Competence in MTs Darul Ulum Lempuyang Pesawaran is the impact of the three strategies are: competence of teachers to be better, more proactive, more disipli teacher, administrative, ethos increased employment, more obedient to the rules, effectively prepares the device, increasing student achievement, and teacher morale up date more IT- based learning strategies